Nanoparticle Exsolution from Nanoporous Perovskites for Highly Active and Stable Catalysts. Issue 6 (22nd January 2023) - Rudolph, Benjamin; Tsiotsias, Anastasios I.; Ehrhardt, Benedikt; Dolcet, Paolo; Gross, Silvia; Haas, Sylvio; Charisou, Nikolaos D.; Goula, Maria A.; Mascotto, Simone
Abstract: Nanoporosity is clearly beneficial for the performance of heterogeneous catalysts. Although exsolution is a modern method to design innovative catalysts, thus far it is predominantly studied for sintered matrices. A quantitative description of the exsolution of Ni nanoparticles from nanoporous perovskite oxides and their effective application in the biogas dry reforming is here presented. The exsolution process is studied between 500 and 900 °C in nanoporous and sintered La0.52 Sr0.28 Ti0.94 Ni0.06 O3± δ . Using temperature‐programmed reduction (TPR) and X‐ray absorption spectroscopy (XAS), it is shown that the faster and larger oxygen release in the nanoporous material is responsible for twice as high Ni reduction than in the sintered system. For the nanoporous material, the nanoparticle formation mechanism, studied by in situ TEM and small‐angle X‐ray scattering (SAXS), follows the classical nucleation theory, while on sintered systems also small endogenous nanoparticles form despite the low Ni concentration. Biogas dry reforming tests demonstrate that nanoporous exsolved catalysts are up to 18 times more active than sintered ones with 90% of CO2 conversion at 800 °C. Time‐on‐stream tests exhibit superior long‐term stability (only 3% activity loss in 8 h) and full regenerability (over three cycles) of the nanoporous exsolved materials in comparison to a commercial Ni/Al2 O3 catalyst. Abstract : The design of nanoporous oxides represents an appealing strategy for the development of exsolved materials. Herein, the process of metal exsolution from nanoporous perovskite oxides is thoroughly described and compared to the one from sintered matrices. The combination of support nanoporosity with the exsolution of metal nanoparticles leads to high‐performing, stable, and regenerable heterogeneous catalysts for biogas dry reforming.